Pengaruh Modal Usaha, Biaya Dan Jenis Kelamin Terhadap Pendapatan Pedagang Pasar Tradisional - Sri Hapsa Uge; Tri Handayani Amaliah; Muliyani Mahmud (Jambura Accounting Review, 2022)
This study aims ti determine the influence of venture capital, funding, an gender on the seller’s uincome in the traditional market in Molutabu Village. This primary research data implement a quantitative method and take 69 respondents through the questionnaire with a simple random sampling technique. This study conducts multiple regression analysis technique with statistical test (validity, reliability, classic assumption, partial, simultaneous,and determination coefficient test). Based on the partial test, it obtains the venture, capital gives positive and significant influence toward the seller’s income, funding or budget gives negative and significantinfluence, and gender has no contribution toward the seller’s incomes in Tradisional Market in Molutabu Village. Venture capital, funding and sex/gender variables simultaneously and significantly influence the seller’s incomes with determination coefficient of 61,4%. It meants that the income variable can be explained by venture capital, funding and gender.